Delicious - Foster, Lori Foster, Lori; Foster, Lori, 1958-; Monroe, Lucy, 1967-; Title, Sarah; Foster, Lori, 1958-; Monroe, Lucy, 1967-; Title, Sarah (New York, NY : Kensington Publishing Corp., 2013)
With a full moon hanging over the apple orchards of Delicious, Ohio, romance is in the air, and three couples are about to experience the magic of falling in love.
Once in a blue moon / Lori Foster -- Moon magnetism / Lucy Monroe -- Full moon pie / Sarah Title.
Keywords: Foster, Lori; Love stories, American; Love stories, American; Short stories